Hubungan Kemampuan Pemecahan Masalah Materi Pemanasan Global dengan Sikap Peduli Lingkungan Setelah Pembelajaran PBL - Meldiana, Mela; Oktarisa, Yuvita; M, Yus Rama Denny (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to investigate the relationship between problem-solving abilities in global warming material and environmental concern attitudes after Problem Based Learning (PBL) instruction. The research method employed a correlation design with the research subjects consisting of 30 students from class X-G SMA Negeri 2 Pandeglang, selected through purposive sampling techniques based on specific criteria, namely students who have undergone PBL instruction on global warming. The research instrument was a questionnaire, and data were analyzed using the pearson product moment correlation test. The research findings indicate a relationship between problem-solving ability and environmental concern attitudes after PBL learning, with a significance value of 0,001 < 0,05 ( accepted). The correlation value ( ) between these two variables is 0,564, indicating a moderate level of association and showing a positive relationship between problem-solving ability and environmental attitudes. Additionally, the contribution of problem-solving ability to attitudes is 31,8%.